PENGARUH PROMOSI, HARGA, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Nadwatul Haramaini; N. Rachma; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTPurchasing decision is a consumer process when making a purchase. In this study will analyze the influence of promotion, price, brand image and quality of product to the decision of purchasing case studies on the consumer shop Donatello Jl. Kawi Malang. This method of analysis is to use a double linear regression analysis of hypothesis testing using T (partial) tests and F (simultaneous) tests.n Simultaneous hypothesis test results show that the promotion, price, brand image and product quality are simultaneously influential to the purchase decision. While the partial indicates that the price is positive and it is significant, the promotion and brand image has a positive influence but not significant but the quality of product has negative influence and insignificant.Keywords: Purchase Decision, Promotion, Price, Brand Image, Product Quality.